EFEK PEMBERIAN SENAM LANSIA TERHADAP PERUBAHAN LINGKAR PINGGANG LANSIA DESA JEGU TABANAN - susy purnawati; I PG adiatmika; made muliarta; ratna sundari; krisna dinata; indah adiputra; adiartha g; D A inten; I D P sutjana; K tirtayasa; J A pangkahila (Sport and Fitness Journal, 2016)
Elderly people, a population group whose age is more than 60 years or older is a group ofpeople who potentially suffered by metabolic disorders due to changes in body fat percentageand the degeneration process. Elderly gymnastics showed theoretically significantly lowered thepercentage of body fat that result in a decrease in waist circumference, increasing the capacityof the memory function, and mental efficiency. This study was a pre-experimental study, carriedout in the Jegu Tabanan Village in February 2014 to September 2015 with a sample of 63 elderly.An abnormal waist circumference (central obesity) defined of > 90 cm in men and > 80 cm inwomen. The data were measured before and after the intervention (elderly gymnastic training)for the six months (once a week, in the morning, at the village hall (Balai Banjar) of JeguTabanan Village, and was guided by an elderly gymnastic instructor. Study result: the studyconsisted of 63 subjects which was 35 (55.6%) men and 28 (45.4%) women with the mean of age was 65 ± 0.5 years old and the mean of BMI was 22.5 ± 3.02 (kg / m2). The results of thebivariate statistical analysis by paired t-test showed a significant difference between waistcircumference before and after giving elderly gymnastics for six months with the value of p =0.023 (CI: 0.449; 5.773). Also we found reduction in waist circumference of 3 cm (3.6%).